2015
DOI: 10.5604/00306657.1147032
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular artery pedicled flap in reconstruction of pharyngocutaneous fitulas after total laryngectomy

Abstract: The aim of the study was to analyze the efficacy of treatment of closure of cutaneopharyngeal fistulas, following total laryngectomy, using a fasciocutaneous flap. In the group of 6 patients treated in years 2013-2014, in 4 (67%) patients the healing process was successful, in one patient complete flap necrosis was noted on the 6th day, in another patient a small cutaneopharyngeal fistula was recognized, which closed secondarily with no intervention. Flaps of this type, having a small risk of local complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…For tracheostoma reconstructions, Chu et al 65 argued that the SCF should be a first-line choice compared with other pedicled flaps such as the pectoralis major myocutaneous flap or the deltopectoral flap. These flaps are bulky and could narrow the airway stoma and hinder speech rehabilitation by preventing the insertion of a prosthetic devices 57,65 . Using the PMMF for oral reconstruction may even require segmental mandibulectomy to accommodate flap mass, however, even with this modification, patients may still experience compression 52 …”
Section: Resultsmentioning
confidence: 99%
“…For tracheostoma reconstructions, Chu et al 65 argued that the SCF should be a first-line choice compared with other pedicled flaps such as the pectoralis major myocutaneous flap or the deltopectoral flap. These flaps are bulky and could narrow the airway stoma and hinder speech rehabilitation by preventing the insertion of a prosthetic devices 57,65 . Using the PMMF for oral reconstruction may even require segmental mandibulectomy to accommodate flap mass, however, even with this modification, patients may still experience compression 52 …”
Section: Resultsmentioning
confidence: 99%
“…14 In another study of six patients reconstructed with the SCAIF for repair of pharyngocutaneous fistulae after laryngectomy, one patient experienced complete flap necrosis, and one had a recurrent fistula. 15 In contrast, two different studies examining a total of nine patients with oropharyngeal defects reported no flap loss in the postoperative period. 16,17 In contrast to our findings and selected reports in the literature, many authors have reported good success with the supraclavicular island flap for mucosal reconstruction.…”
Section: Discussionmentioning
confidence: 96%
“…Many authors suggest that reinforcing the pharyngeal suture with wellvascularized tissue will help to reduce the incidence of PCF formation in these patients (5,29,30). The pectoralis major myofascial flap is one of the most reliable flaps, but many other reconstructive options are described (supraclavicular artery island flap, fasciocutaneous free flaps, mammary artery perforator propeller flap, latissimus dorsi flaps, and facial artery-based cutaneous island flap) (21,22,(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%